Interface behaviors and mechanical properties of diffusion bonded 45 steel/additive manufactured 316L steel joints - Ruiwen Xu; Yi Zhu; Bingnan Li; Huayong Yang; Chao Zhang (Journal of Materials Research and Technology, 2024)
Diffusion bonding of additive manufactured (AM) metal parts to traditionally manufactured metal parts could simultaneously achieve large-scale, complex-structure, and multi-material parts. However, there is a lack of study on diffusion bonding as well as its interface formation mechanism between AM metal parts and traditionally manufactured metal parts. In this study, diffusion bonding was performed to join AM 316L stainless steel and casting 45 steel at different temperatures. The element distribution, interface characteristics and shear strength of the joints were investigated, and the interface formation mechanism at different bonding temperature was analyzed in detail. The results reveal that the interface transition zone from the AM 316L steel side to the 45 steel side is composed of the metallic elements diffusion layer and the carbide layer. Moreover, an increase in bonding temperature can effectively promote interface voids closure and increase the thickness of the metallic elements diffusion layer, while the thickness of the carbide layer firstly increases and then decreases as the temperature increases. The component of the carbide layer was identified as brittle compounds (CrFe)23C6 and (CrFe)7C3. The shear strength of the joints exhibited an increasing trend with the increasing bonding temperature. Interestingly, a sudden decrease in strength was found at 950 °C due to the significant increase of the brittle carbide layer, while high-quality joints could be achieved as the brittle carbides dissolve at 1000 °C. This study could lay the foundation for understanding diffusion bonding interface behaviors between AM metal parts and traditional casting metal parts.